Nanocomposite Films: Optically Transparent and Low‐CTE Polyethersulfone‐Based Nanocomposite Films for Flexible Display (Adv. Mater. Interfaces 24/2020). Issue 24 (17th December 2020) - Kim, Jae‐Hyun; Lan, Nguyen Xuan Viet; Kulkarni, Uddhav; Kim, Chanho; Cho, Sung Min; Yoo, Pil J.; Kim, Dukjoon; Schroeder, Marc; Yi, Gi‐Ra
Abstract : In article number 2001422, Gi‐Ra Yi and co‐workers introduce a polyethersulfone (PESU)‐nanoparticle composite film for flexible OLED. Chemically coupled nanoparticle‐polymer composite films are prepared by a heat pressing process which enhance thermomechanical properties significantly. Notably, the nanocomposite films are optically transparent by matching refractive index between nanoparticles and polymer.